Infections with Schistosoma mansoni and geohelminths among school children dwelling along the shore of the Lake Hawassa, southern Ethiopia - Tadege, Bamlaku (PLoS One, 2017)
BACKGROUND: Infections with Schistosoma mansoni and soil-transmitted helminthes (STHs) are major public health problems in Ethiopia. However, information was scarce on the current status of these infections to guide an intervention in the study area. Therefore, this study was conducted to assess the prevalence of infections with S. mansoni and STHs and associated factors among school children in southern Ethiopia. METHODS: This cross-sectional study investigated children who were attending the Finchawa and Tullo junior elementary schools and were residing along the shore of the lake Hawassa in January and February, 2015. A total of 374 students were selected using systematic random sampling technique. Data on socio-demography and related factors was collected using structured questionnaires. A single stool sample was collected from each child and processed using formol-ether concentration technique and examined microscopically for parasites’ ova/larva. RESULTS: The prevalence of parasitic infection with one or more than one helminthiasis was found to be 67.9%. Seven different types of helminths were identified and the most prevalent parasites were Ascaris lumbricoides (44.4%), followed by S. mansoni (31%), Trichuris trichiura (11%), and hookworms (7.7%). The rate of infection with STHs was 52.4%. Single, double, triple and quadruple infections were 42.2, 22.5, 2.4, and 0.8%, respectively. Children who practiced open-field defecation (AOR, 3.6; 95% CI 1.6–8.0; p = 0.001) and had not always washed their hands before eating a meal (AOR, 5.0; 95%CI 2.15–11.7; p <0.001) were more infected with STHs. Moreover, the rate of S. mansoni infection was significantly higher among children who were attending the Finchawa school (AOR, 2.13; 95% CI 1.31–3.46; p = 0.002), aged 11–15 years (AOR, 1.97; 95% CI 1.22–3.19; p = 0.006), had swum in the lake Hawassa (AOR, 2.73; 95%CI 1.20–6.17; p = 0.016), and had involved in irrigation-related activities (AOR, 1.68; 95%CI 1.04–2.71; p = 0.034). CONCLUSION: The study showed high prevalence of STHs and moderate rate of schisotosomiasis. Mass deworming twice a year for STHs and once every two years for S. mansoni, further to strengthening other prevention measures, is critically needed to reduce these infections to inconsequential level.